2017
DOI: 10.1002/jbm.a.36042
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of bioactivated and antiinfective PDLLA – coated surfaces

Abstract: Common scaffold surfaces such as titanium can have side effects; for example, infections, cytotoxicity, impaired osseointegration, or low regeneration rates for bone tissue. These effects lead to poor implant integration or even implant loss. Therefore, bioactive implants are promising instruments in tissue regeneration. Osteoinductive elements-such as growth factors and anti-infectives-support wound healing and bone growth and thereby enable faster osseointegration, even in elderly patients. In this study, ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 49 publications
(106 reference statements)
0
7
0
Order By: Relevance
“…Under the assumption that previous in vitro results are transferable to in vivo findings, we found that this limited expression level seems to be sufficient to induce NB, because of endogenous BMP‐2 release by nontransfected cells via the paracrine stimulation of cells by the gene‐activated surface within the initial 14 days postsurgery. By the gene therapeutic approach, transgene‐derived low amounts of BMP2 are produced after local transfection of cells which then can activate additional endogenous BMP2 production in non‐transfected target cells …”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Under the assumption that previous in vitro results are transferable to in vivo findings, we found that this limited expression level seems to be sufficient to induce NB, because of endogenous BMP‐2 release by nontransfected cells via the paracrine stimulation of cells by the gene‐activated surface within the initial 14 days postsurgery. By the gene therapeutic approach, transgene‐derived low amounts of BMP2 are produced after local transfection of cells which then can activate additional endogenous BMP2 production in non‐transfected target cells …”
Section: Discussionmentioning
confidence: 68%
“…This transfection process, however, leads to a cascade of cell differentiation and mitosis of transfected osteoprogenitor cells, which thereby enhances GF release over a longer period of time (for detailed data, please refer to Ref. ). Endogenous BMP‐2 expression, evoked by gene vectors, is more physiological in terms of, for example, host‐specific glycosylation, because of de novo synthesis by local host cells …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to chemical modifications, physical modifications of the substrate impact cell-material interactions by altering the interface, yet maintain bulk material properties such as biocompatibility and hardness. Physical characteristics of the substrate have been shown to affect cellular adhesion, spreading, migration, proliferation, and morphology, presumably by spatially confining adsorbed ECM proteins and cells 40,96…”
Section: Physical Modifications That Influence Cellular Responsivenesmentioning
confidence: 99%
“…For example, some applications include coating a vascular stent with poly(lactic-co-glycolic acid) (PLGA) bilayer nanoparticles and DNA encoding vascular endothelial growth factor to prevent restenosis, 34 loading a collagen patch with bPEI and DNA encoding platelet-derived growth factor-BB to increase wound healing, 35 or coating a titanium (Ti) bone implant with poly-(d,l-lactide) and polymer vectors complexed with DNA plasmids encoding bone morphogenetic protein-2 (BMP-2) to encourage osseointegration. 36 To use a cell-material interface to prime cells for more efficient transfection, substrate properties can be tuned through chemical modifications such as the addition of natural coatings, ligands, or functional side groups, and/or physical modifications such as topography or stiffness. The cell-material interface is known to influence cell behaviors that are innately controlled by the extracellular matrix (ECM) proteins 37 that adsorb onto a culture surface or exist natively in tissue.…”
Section: Impact Statementmentioning
confidence: 99%